History learning at secondary school about Demak Kingdom - M Nur Rokhman; Lia Yuliana (Journal of Social Studies (JSS), 2018)
The main problems dealing with history learning has always been correlated with boring and unattractive learning in the classroom. This study aims to find out: the material of the Demak kingdom in learning of history in high school. The research method used in this research is a historical method consisting of five steps, namely topic selection, heuristic, criticism, interpretation, and historiography. The results show that the Demak Sultanate was the first Islamic sultanate in Java, which was founded by Raden Patah in 1478 after Demak was established independently separated from the destroyed Majapahit. The territory of the Demak kingdom includes Jepara, Semarang, Tegal, and lembang, jambi, islands between Kalimantan and Sumatra, as well as several areas on the island of Kalimantan. The important ports controlled by Demak are Jepara, Tuban, Sidayu, Jaratan and Gresik. Demak has an important role in the development of Islam in Java and Demak is the center of the spread of Islam. The people who spread Islam is known as wali. For places of worship and centers of religious activities, wali set up a mosque in Demak. Demak Kingdom experienced a glorious period in the government of Sultan Trenggana who ruled from 1521-1546 M. Sultan Trenggana tried to expand his territory to West Java. In 1522 the Demak Kingdom sent troops to West Java under the leadership of Fatahillah.